A theory of planned behavior perspective on hiring Malaysians with disabilities - Magdalene C.H. Ang; T. Ramayah; Hanudin Amin (Emerald Group Publishing Limited, 2015)
Purpose – The high unemployment rates among persons with disabilities (PWDs) is nothing new. Many people fail to recognize that the disabled population is a significant but largely untapped source of human resources. Prejudices and misconceptions about PWDs’ ability to perform and compete in the open market are likely to be the cause. While the topic of PWDs’ employment has been substantially studied, no known research has explored the applicability of the theory of planned behavior (TPB) in the context of hiring PWDs. In addressing the research gap, this paper details a preliminary study which examined the influence of attitude, subjective norm, and perceived behavioral control on managerial intention to hire Malaysians with disabilities. The paper aims to discuss these issues. Design/methodology/approach – Data were obtained via a survey on 200 employers representing private organizations in East Malaysia. To examine the hypothesized linkages within the TPB framework, the authors conducted PLS analysis. The authors also examined the measurement model using PLS. Findings – The results of the PLS analysis indicated that subjective norm and perceived behavioral control significantly predicted managerial intention to hire Malaysians with disabilities. Contrary to expectations, the data did not provide support for the influence of attitude toward hiring decisions for PWDs. Research limitations/implications – Given the research approach, generalizing the findings must be done with caution. Longitudinal studies may provide further support to the results. Future studies can extend the TPB framework by examining other variables such as attributes of Malaysians with disabilities or those of hiring managers. Hiring behavior can also be included in the model to confirm if behavioral intention of hiring will evidently result in actual hiring of Malaysians with disabilities. Practical implications – This study found the TPB to have a predictive power in the area of hiring PWDs. Results obtained can serve as a basis for future works in this area. The study also offers implications for the development of public and organizational policies that can better promote and manage the careers of Malaysians with disabilities. Social implications – An enhanced knowledge about the factors which can influence managerial intention to hire Malaysians with disabilities will help increase the employment of Malaysians with disabilities. Originality/value – This study is a pioneering attempt to explore the applicability of the TPB within the domain of managerial intention to hire Malaysians with disabilities. The use of PLS in disability studies is also noteworthy.